BACTERIOLOGICAL AND CLINICAL STUDIES OF ME 1207 IN THE FIELD OF SURGERY - Shinagawa, Nagao; Ishikawa, Shu; Yura, Jiro; Mashita, Keiji; Suzui, Katsuya; Ishihara, Hiroshi (CHEMOTHERAPY, 1992)
We performed bacteriological and clinical studies on the newly developed oralcephem antibiotic ME 1207 in the field of surgery to determine the antibacterial activity and clinical efficacy. The results were as follows. (1) Antibacterial activity: The MIC50/MIC9O values (μg/ml) of ME 1206 againstsurgical lesion isolates of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa were 25/100, 0.2/25, 1.56/6.25 and 100/>100, respectively. Against S. aureusand E. coli, ME 1207 was more active than any of the other 3 drugs (cefaclor, cefteram, and cefixime).It was more active than cefaclor and cefteram against K. pneumoniae but slighty less active than cefixime. (2) Transport to bile: After oral administration of ME 1207 (200mg) to 3 subjects its concentration in the bile ranged from 6.9μg/ml to 128μg/ml. The concentration of ME 1207 was higher in the bile than in the blood in all the three subjects, but varied widely among the three individuals. (3) Clinical efficacy: In 35 patients with surgical infections treated with ME 1207, the response was “excellent” in 15 patients, “good” in 14, “fair” in 5, and “poor” in 1. The overall efficacy rate was 82.9%. In the bacteriological study the causative pathogens were isolated from 25 patients and were eradicated in 23 of them, unchanged in 1 and replaced in 1. The rate of bacterial eradication was 96.0%. Neither subjective nor objective side effects were observed. Abnormal laboratory tests, such as mild eosinophilia and slight elevations in GOT and GPT were respectively observed in one patient each but these abnormality had no serious clinical implications in any of thepatients.